Microvascular cerebral blood flow response to intrathecal nicardipine is associated with delayed cerebral ischemia - Sathialingam, Eashani; Cowdrick, Kyle R.; Liew, Amanda Y.; Fang, Zhou; Lee, Seung Yup; McCracken, Courtney E.; Akbik, Feras; Samuels, Owen B.; Kandiah, Prem; Sadan, Ofer; Buckley, Erin M. (Frontiers in Neurology, 2023)
One common complication of non-traumatic subarachnoid hemorrhage is delayed cerebral ischemia. Intrathecal administration of nicardipine, a calcium channel blocker, upon detection of large-artery cerebral vasospasm holds promise as a treatment that reduces the incidence of delayed cerebral ischemia. In this observational study, we prospectively employed a non-invasive optical modality called diffuse correlation spectroscopy to quantify the acute microvascular cerebral blood flow response to intrathecal nicardipine (up to 90 min) in 20 medium-high grade non-traumatic subarachnoid hemorrhage patients. On average, cerebral blood flow increased significantly with time post-administration. However, the cerebral blood flow response was heterogeneous across subjects. A latent class mixture model was able to classify 19/20 patients into two distinct classes of cerebral blood flow response: patients in Class 1 (n=6) showed no significant change in cerebral blood flow, while patients in Class 2 (n=13) showed a pronounced increase in cerebral blood flow in response to nicardipine. The incidence of delayed cerebral ischemia was 5/6 in class 1 and 1/13 in class 2 (p<0.001). These results suggest that the acute (<90 min) DCS-measured CBF response to IT nicardipine is associated with intermediate term (up to 3 weeks) development of delayed cerebral ischemia.